SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN DANA SIMPAN PINJAM PEREMPUAN (SPP) PNPM MENGGUNAKAN METODE ELECTRE - Gusmita, Devi; Rianti, Eva (Jurnal Sains Informatika Terapan, 2024)
The Women's Savings and Loans Program is one of the Indonesian government's efforts to develop rural savings and loans opportunities, strengthen women's institutions, and encourage the reduction of poor households and job creation. The decision support system for the selection of recipients of women's savings and loans funds aims to determine the profitability of lending to women's groups in UPK in North Rao district. Suboptimal decision-making can interfere with the provision of women's savings and loans funds. This system is made by the Electre method (Elimination et choix traduisantla realite). The aim is to help the UPK of Pohjois Rao Subdistrict to provide objective and targeted assistance based on different levels of importance from each criterion. System created using the Electre method, (Elimination et choix traduisantla realite). The aim is to help the North Rao Subdistrict UPK provide assistance objectively and purposefully based on different levels of importance from each criterion. Calculations are carried out for each criterion in this system, which then shows the rating results from the highest to the lowest, so that it can be used as a reference for UPK to determine borrowers.